Aspects of private labels development in the segment of organic food in Czech Republic - Olga Kutnohorská; Marek Botek (Contemporary Economics, 2010)
The article deals with various aspects of the private labels building. It primarily focuses on organic food market in the Czech Republic, but on this market it illustrates the general trends, both in brand building, as well as in the importance of a brand in purchasing decisions. Organic food market is specific as there is high importance of product attributes, which are based on customer's confidence. Many of the important criteria for the decision to purchase (the way of cultivation and processing of food, freshness, taste, etc.) are not possible to be objectively assessed before buying. A brand name plays a large role in the confidence based attributes. Consumers perceive it as a certain guarantee of the expected quality. In the field of organic food there are still not strong brands but there is the space and the need to differentiate organic from conventional foods, in particular. A suitable option could be the retail chain private labels, which are already partially developed as far as for consumers subconscious expectations are concerned. The final part of the article provides an overview of the current offer of organic food private labels in the Czech Republic.
Keywords: 330